Membentuk Karakter Siswa melalui Pembelajaran Matematika Berbasis Budaya Lokal Tapanuli - Marzuki Lubis; Khoiruddin Saleh Siregar; Sabri; Afdhal Ilahi; Eva Yanti Siregar; Dwi Putria Nasution (Institut Pendidikan Tapanuli Selatan, 2022)
The Community Service activities carried out aim to shape the character of students through teaching and learning mathematics activities using the concept of local local culture. The subjects of the activity were students of the 200201 Padangsidimpuan State Elementary School which consisted of 24 students. The object of the activity is the formation of student character based on local culture. Activities are carried out in the form of mentoring students in learning mathematics based on local culture which includes giving lectures, discussing questions and drawing conclusions. Data was collected by using descriptive qualitative method. Through the activities carried out, it was concluded that through cultural-based mathematics learning, students' character was formed, especially in cooperation, hard work, responsibility and caring. The character of cooperation can be formed when students work together in understanding subject matter and problem solving, hard work is formed in students through discussing difficult problems presented, responsibility is formed on students when students understand what must be done and understand the intent and purpose of the work. implemented, and care is formed in students when students are accustomed to sharing information in learning activities. Keywords: Character, Learning, Mathematics, Local culture. Abstrak Kegiatan Pengabdian kepada Masyarakat yang dilakukan bertujuan untuk membentuk karakter siswa melalui kegiatan belajar mengajar matematika dengan menggunakan konsep budaya lokal setempat. Subjek dari kegiatan adalah siswa Sekolah Dasar Negeri 200201 Padangsidimpuan yang terdiri dari 24 siswa. Objek kegiatan adalah pembentukan karakter siswa berdasarkan budaya lokal. Kegiatan dilaksanakan dalam bentuk pendampingan siswa dalam pembelajaran matematika dengan berbasis budaya lokal yang meliputi kegiatan pemberian ceramah, pembahasan soal dan penarikan kesimpulan. Pengumpulan data dilakukan dengan metode kualitatif deskriptif. Melalui kegiatan yang dilakukan diperoleh kesimpulan bahwa melalui pembelajaran matematika berbasis budaya yang dilakukan terbentuk karakter siswa khususnya pada kerjasama, kerja keras, tanggung jawab dan peduli. Karakter kerjasama dapat terbentuk pada saat siswa bekerja sama dalam memahami materi pelajaran dan pemecahan masalah, Kerja keras terbentuk pada siswa melalui pembahasaan permasalahan permasalahan sulit yang disajikan, tanggung jawab terbentuk pada siswa ketika siswa memahami apa yang harus dikerjakan serta memahami maksud dan tujuan pekerjaan tersebut dilaksanakan, dan peduli terbentuk pada siswa ketika siswa terbiasa dalam kegiatan berbagi informasi dalam kegiatan pembelajaran. Kata Kunci: Karakter, Pembelajaran, Matematika, Budaya lokal.